Cold Non-equilibrium Plasma as a Tool for Air Disinfection and Destruction of Biological Objects - Ponizovskiy, Alexander Z.; Plochov, Alexander Vasilevich (Current Biotechnology, 2023)
Introduction: The paper presents the results of experiments on the purification of air contaminated with S. aureus, as well as the destruction of yeast under the action of cold nonequilibrium plasma of a nanosecond streamer corona discharge.Methods: It is shown that plasma is an effective means for destroying both bacteria in the air and biological objects on the surface. The main parameters of the nanosecond streamer corona discharge and their relationship with the operating time of the active plasma components were determined. It was experimentally established that the inactivation time of 80% of S. aureus bacteria with a concentration of 2.1104 KOE m-3 was 0.4 s with a specific energy of 28 Jl-1.Results: The results of measurements of the dependence of the yeast destruction degree on the yeast size, the time of direct exposure to the nanosecond streamer corona discharge, active elements of cold nonequilibrium plasma, and third-party ultraviolet radiation are presented.Conclusion: A comparison of the results of air disinfection experiments with data on yeast destruction shows that the latter can be used for rapid analysis of the effects of low-temperature plasma on other biological objects.
Keywords: electromagnetic feild